2022
DOI: 10.3390/children9010114
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Health Promoting Bacteria in the Gastrointestinal Microbiome of PICU Infants with Bronchiolitis: A Single-Center Feasibility Study

Abstract: The feasibility of gastrointestinal (GI) microbiome work in a pediatric intensive care unit (PICU) to determine the GI microbiota composition of infants as compared to control infants from the same hospital was investigated. In a single-site observational study at an urban quaternary care children’s hospital in Western Michigan, subjects less than 6 months of age, admitted to the PICU with severe respiratory syncytial virus (RSV) bronchiolitis, were compared to similarly aged control subjects undergoing proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Several studies have shown that, in critically ill patients, dysbiosis (disruption of the microbiota homeostasis due to an imbalance in the microflora) involves the loss of health benefits from disappearing commensal bacteria and the overgrowth by pathogenic strains [150][151][152][153][154]. Pathogenic E. coli can cause diarrhea and has also been observed in critically ill patients requiring ICU support [155,156].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that, in critically ill patients, dysbiosis (disruption of the microbiota homeostasis due to an imbalance in the microflora) involves the loss of health benefits from disappearing commensal bacteria and the overgrowth by pathogenic strains [150][151][152][153][154]. Pathogenic E. coli can cause diarrhea and has also been observed in critically ill patients requiring ICU support [155,156].…”
Section: Discussionmentioning
confidence: 99%
“…Of the remaining 225 articles, the number of ineligible articles after the review of titles and abstracts was 189. A full-text review was performed for 36 articles, and 12 articles (respiratory tract microbiome: 9; gut microbiome: 2; both: 1) met the inclusion criteria and were included in this review [ 26 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. A full list of reasons for exclusion is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the included studies are shown in Table 1 (respiratory tract microbiome compared to healthy controls), Table 2 (gut microbiome), and Table S2 (respiratory tract microbiome compared to patients other than healthy controls). All of the studies were conducted in industrialized countries: the United States of America ( n = 8) [ 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], Spain ( n = 1) [ 29 ], Italy ( n = 1) [ 39 ], the Netherlands ( n = 1) [ 31 ], and China ( n = 1) [ 26 ]. Although five of the studies included in this review were multicenter studies, no studies were conducted in multiple countries [ 31 , 32 , 34 , 35 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations